Relevansi Amandemen UUD 1945 terhadap Tuntutan Era Globalisasi - Jawahir Thontowi (Fakultas Hukum Universitas Islam Indonesia, 1999)
Political practice, both in the periods of the Old Regime and New Regime, did not reflect the implementation of Rule of Law principles. Government system tended to be constitutionalism authoritarian, indicated by an abundance of legislation justfying government policies. The amandement of the Constitution of 1945, There fore, has been relevantin the era of globalization not only for the sake ofhuman right protection, good relationshipamong of ethnics, religions and groups as well as of universal values, but also for the sake of greater as surance to form the supremacy of law.